The Handy Eye Check: a mobile medical application to test visual acuity in children - Toner, Keri N.; Lynn, Michael J.; Candy, T. Rowan; Hutchinson, Amy K. (Journal of AAPOS, 2014)
To compare visual acuity results obtained with the Handy Eye Chart to results obtained using the Handy Eye Check, a mobile medical application that electronically presents isolated Handy Eye Chart optotypes according the Amblyopia Treatment Study (ATS) protocol. Consecutive patients 6-18 years of age presenting for eye examinations between May 30, 2012, and June 26, 2012, were invited to participate. Monocular visual acuity testing was performed on the subject's poorer-seeing eye using both the Handy Eye Check and the Handy Eye Chart under the same conditions. Visual acuity was first tested using the mobile application, then using the chart, followed by repeated application testing. Patients were excluded if they were unable to undergo the required visual acuity testing or if visual acuity in the worse-seeing eye was less than 20/200 (for validity testing, but not reliability testing). There was a strong linear correlation (r = 0.92) and a mean difference in acuity of −0.005 logMAR, or less than one letter (95% CI, −0.03 to 0.02), between the two tests. The 95% limits of agreement were ± 2 lines. Test–retest reliability was high, with 81% of retest scores within 0.1 logMAR (5 letters) and 100% within 0.2 logMAR (10 letters), an intraclass correlation coefficient of 0.93, and a standard error of measurement of 0.08. The Handy Eye Check mobile application compares similarly to the Handy Eye Chart as a valid and reliable test of visual acuity in children age 6-18 years.▪